Monopoly by Contract: The Practice of Franchised Fee and Royalty Rate - Ramjerdi, Maria Hamideh (Journal of Reviews on Global Economics, 2014)
This paper uses a theoretical framework and a by use of a franchising model will examine the practice of charging a franchise fee for the use of the trademark and will show how this practice by controlling the number of franchised operations enables franchisor to extract monopoly profit. Paper will further examine the conditions which the joint practice of franchise fee and royalty rate allows extraction of monopoly rent.